2012
DOI: 10.1016/j.cmet.2012.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Supplementation Does Not Improve Metabolic Function in Nonobese Women with Normal Glucose Tolerance

Abstract: Summary Resveratrol has been reported to improve metabolic function in metabolically-abnormal rodents and humans, but has not been studied in non-obese people with normal glucose tolerance. We conducted a randomized, double-blind, placebo-controlled trial to evaluate the metabolic effects of 12 weeks of resveratrol supplementation (75 mg/day) in non-obese, postmenopausal women with normal glucose tolerance. Although resveratrol supplementation increased plasma resveratrol concentration, it did not change body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
301
4
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 342 publications
(318 citation statements)
references
References 35 publications
12
301
4
1
Order By: Relevance
“…In the other RCT with (resVida ® ) intake of 75 mg trans-resveratrol of the Novel Food per day over 12 weeks was studied in 30 healthy non-obese postmenopausal women with normal glucose tolerance. No effects were observed on the resting metabolic rate, body composition, plasma lipids, inflammatory markers and insulin sensitivity (Yoshino et al, 2012). Both studies included clinical chemistry and haematological testing of blood samples and reported that no adverse effects have been observed.…”
Section: Human Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the other RCT with (resVida ® ) intake of 75 mg trans-resveratrol of the Novel Food per day over 12 weeks was studied in 30 healthy non-obese postmenopausal women with normal glucose tolerance. No effects were observed on the resting metabolic rate, body composition, plasma lipids, inflammatory markers and insulin sensitivity (Yoshino et al, 2012). Both studies included clinical chemistry and haematological testing of blood samples and reported that no adverse effects have been observed.…”
Section: Human Studiesmentioning
confidence: 99%
“…Both studies included clinical chemistry and haematological testing of blood samples and reported that no adverse effects have been observed. The Panel notes the short study duration (Timmers et al, 2011) and the low dose studied by Yoshino et al (2012) compared to the use level intended by the applicant.…”
Section: Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, in humans, it is conjugated rapidly and completely following absorption; despite reasonably efficient absorption, orally administered resveratrol does not appear to achieve sustained serum levels of free resveratrol sufficient to inhibit mitochondrial ATP synthase and thereby activate AMPK (Walle et al 2004;Boocock et al 2007). Consistent with this, several recent controlled clinical studies have failed to observe an impact of oral resveratrol on insulin sensitivity, blood pressure, body composition, or other clinical parameters; in addition, AMPK activity in skeletal muscle or adipocytes was not influenced (Yoshino et al 2012;Poulsen et al 2013). However, oral resveratrol might have the potential to transiently activate AMPK in the intestinal mucosa.…”
Section: Practical Strategies For Implementing Ampk Activationmentioning
confidence: 63%
“…Recently it was also shown that 30 days of resveratrol supplementation improved some markers of mitochondrial function in muscle of obese subjects, in parallel with improved HOMA-IR and reduced hepatic lipid levels [230]. These effects seem to be limited to metabolically compromised subjects, as resveratrol did not improve markers of glycaemic control in non-obese women with normal glucose tolerance [231]. An alternative approach to using direct SIRT1 activators to mimic calorie restriction, is to increase the intracellular levels of NAD + , the obligate co-factor for the sirtuin reaction.…”
Section: Caloric Restriction and Modulation Of Sirtuin Enzymesmentioning
confidence: 94%